Parallel Imports and Manufacturer Rebates - Laura Birg (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
This paper studies the effect of a change in the mandatory manufacturer rebate on wholesale prices for pharmaceuticals on competition by parallel imports. First, it analyzes the effect of a manufacturer rebate on competition by parallel imports in a two-country model. An increase in the manufacturer rebate increases the market share of parallel imports. Second, the paper exploits a policy reform in Germany in 2010, which increased the manufacturer rebate by 10 percentage points. Using a data set with prescription drugs with competition from parallel imports, I estimate the eect of the change in the manufacturer rebate on competition by parallel imports. Estimation results suggest that an increase in the manufacturer rebate has increased the market share of parallel imports and the number of importers.
Keywords: F12; I11; I18; F12; I11; I18; 330; parallel imports; manufacturer rebate; pharmaceuticals; regulation